Nové poznatky v problematice divertikulární choroby tracníku - Dolejsí, Mojmír (Casopis lekaru ceskych, 2011)
The article is a summary paper aimed at new knowledge, concerning the classification, diagnostics, medication and endoscopic treatment of diverticular disease of colon. Briefly mentioned are the issues of functional disorder in the field of diverticulosis--symptomatic uncomplicated diverticular disease of colon. Diverticular bleeding is explained in terms of its pathogenesis and diagnostics. The problem with estimation the ration of diverticular bleedings in the total number of bleedings into the lower digestive tract is caused by diverse criteria for selecting patients and two levels of diagnostic of diverticular bleeding (definite and presumptive). Attention is paid also to diverticular colitis. Synonyms, endoscopic and histological classification are listed. The main endoscopic findings represent areas of erythema, which are visible on the mucosa between diverticula. Diverticulitis is seen as the most significant complication and the diagnostics of diverticulitis is discussed in detail. The first recommended step in the diagnosis is an urgent abdominal ultrasound; the gold standard is a CT examination of the abdomen, in special situations, some other imaging methods should be used: MRI, colonoscopy. The article ends with an overview of modern therapeutic options in the treatment of diverticular colitis and diverticulitis, particularly the use of antibiotics, probiotics, mesalasine and antispasmodics. Negative effect of NSAIDs on the course of diverticulitis and induction diverticular bleeding is listed.
Keywords: lidé; divertikl tlustého střeva; Humans; Diverticulum, Colon